2022
DOI: 10.1038/s42003-022-03678-1
|View full text |Cite
|
Sign up to set email alerts
|

Seed choice in ground beetles is driven by surface-derived hydrocarbons

Abstract: Ground beetles (Coleoptera: Carabidae) are among the most prevalent biological agents in temperate agroecosystems. Numerous species function as omnivorous predators, feeding on both pests and weed seeds, yet the sensory ecology of seed perception in omnivorous carabids remains poorly understood. Here, we explore the sensory mechanisms of seed detection and discrimination in four species of omnivorous carabids: Poecilus corvus, Pterostichus melanarius, Harpalus amputatus, and Amara littoralis. Sensory manipulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 98 publications
0
2
0
Order By: Relevance
“…Ground‐dwelling beetles are useful bioindicators because of their quick response to environment change (Rainio & Niemelä, 2003). Further, some of ground‐dwelling beetles are known as seed predators and can mediate seed dispersal (Ali et al, 2022; de Vega et al, 2011; Griffiths et al, 2016; Müller et al, 2022), and even some fungi are dispersed by ground‐dwelling beetles (Heitmann et al, 2021; Vašutová et al, 2019). Moreover, plant growth enhancement by some species of ground‐dwelling beetles through improving soil quality was reported (Nichols et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Ground‐dwelling beetles are useful bioindicators because of their quick response to environment change (Rainio & Niemelä, 2003). Further, some of ground‐dwelling beetles are known as seed predators and can mediate seed dispersal (Ali et al, 2022; de Vega et al, 2011; Griffiths et al, 2016; Müller et al, 2022), and even some fungi are dispersed by ground‐dwelling beetles (Heitmann et al, 2021; Vašutová et al, 2019). Moreover, plant growth enhancement by some species of ground‐dwelling beetles through improving soil quality was reported (Nichols et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…(Ali and Willenborg, 2021;Foffová et al, 2020;Gaba et al, 2019;Honek et al, 2007). It has been recently suggested that the primary sensory mechanism used by carabid beetles to detect and distinguish seeds is olfactory perception and that final choice is determined by surface-derived hydrocarbons (Ali et al, 2022). Thus, foraging in carabid beetles is likely an active process guided by specific sensory information gathered from the environment to assess overall food quality (Ali et al, 2022;Kielty et al, 1996;Law and Gallagher, 2015;Tréfás et al, 2001).…”
Section: Discussionmentioning
confidence: 99%